Bidirectional Associations between Sport Involvement and Mental Health in Adolescence - Vella, Stewart A; Vella, Stewart A. (My University, 2017)
Purpose This study aimed to investigate potential bidirectional relationships between sport participation and mental health during early adolescence. Methods Data were taken from wave 5 (2012) and wave 6 (2014) of the K cohort of the Longitudinal Study of Australian Children. In total, there were 4023 participants (mean age = 12.41 yr, SD = 0.49 yr, at baseline), and this sample was followed up 24 months later. Cross-lagged panel models were used to examine bidirectional relationships between sport participation (hours per week for team, individual, and total sport participation) and mental health (total psychological difficulties, internalizing problems, and externalizing problems) as measured by the parent-report version of the Strengths and Difficulties Questionnaire (SDQ). Results Bidirectional relationships were evident between time involved in sport and overall mental health (Sport12→SDQ14: β = −0.048; SDQ12→Sport14: β = −0.062). Bidirectional relationships were also evident between time involved in sport participation and internalizing (social and emotional) problems (Sport12→SDQ14: β = −0.068; SDQ12→Sport14: β = −0.067). The relationship between time in organized sport and externalizing problems (conduct problems and inattention/hyperactivity problems) was not bidirectional. Externalizing problems predicted later sports participation (β = −0.039), but not vice versa. Conclusion Findings demonstrate bidirectional relationships between sport participation and adolescent mental health. The design and implementation of youth sport programs should maximize mental health benefits, and programs should be designed, implemented, and marketed to be attractive to participants with poor psychosocial health.
Keywords: Health -- Mental; Relationships; Actvities -- Children's activities; Childhood and child development; Health and wellbeing; Actvities; Health; Relationships; Children's activities; Mental; Childhood and child development; Health and wellbeing